Allergen immunotherapy for the control of moderate to severe allergic asthma: an evidence-based conjoint analysis to define candidate patient profiles in Spain and Portugal - Delgado, J.; Cárdenas, R.; Gelis, S.; Domínguez-Ortega, J. (Frontiers in Allergy, 2025)
IntroductionAllergen immunotherapy (AIT) is an effective and safe treatment; however, it is not recommended in consensus guidelines for severe allergic asthma patients. As AIT has been shown to be capable of modifying the course of the disease, it should be considered a concomitant treatment for specific asthma patients. This study aimed to define the profile of patients with severe allergic asthma who are most likely to benefit from AIT.MethodsA conjoint analysis approach was adopted to comprehensively assess the importance of clinical attributes in therapeutic decision-making. A scientific committee selected the main attributes to be considered: lung function, clinical control of allergic asthma, current main treatment and etiological confirmation of moderate to severe allergic asthma. Using the fractional factorial analysis technique, 8 eligible patient profiles for AIT were defined. Participant allergists, by means of a questionnaire, classified the profiles in order of preference, mimicking the comprehensive assessment performed in clinical practice.Results91 allergists from Spain and Portugal with experience in asthma and AIT participated in the study. Allergists gave greater importance to the clinical control of allergic asthma (relative importance of 51.6%), followed by preserved lung function (relative importance of 25.0%), thus confirming that the most important criterion was good control of the underlying asthmatic condition.ConclusionsThe expert allergists endorse the use of AIT in the management of moderate to severe allergic asthma in patients with appropriate clinical characteristics. Additional studies to further investigate the safety and effectiveness of this new therapeutic approach would be of interest.